Multimodality Bronchoscopic Imaging of Recurrent Respiratory Papillomatosis - Colt, Henri G. (2010)
OBJECTIVE/HYPOTHESIS: Recurrent respiratory papillomatosis (RRP) of the central airways requires removal in order to potentially reduce recurrence and risk for malignant transformation. Analogous to the principles of treatment for early lung cancer, a precise determination of the extent of cartilage invasion could help guide therapeutic decisions and monitor response to treatment. The purpose of this study was to determine whether a bronchoscopy platform comprised of white light bronchoscopy (WLB), endobronchial ultrasound (EBUS), and optical coherence tomography (OCT) could identify layered microstructure of RRP and underlying cartilage. STUDY DESIGN: Case study METHODS: A bronchoscopy platform consisting of commercially available WLB, EBUS using a 7.5MHz convex probe (BF-UC 160F: Olympus Optical Co. Ltd, Tokyo, Japan) and a time-domain OCT with front-imaging and inside-actuation (Niris® Imaging system, Imalux® Corp, Cleveland, USA) was used in a patient with tracheal stenosis from RRP. Findings are compared with results of histology and the characteristics of imaging modalities are discussed. RESULTS: WLB revealed tracheal pedunculated lesions. EBUS showed a 1 cm hypoechogenic density corresponding to the papilloma, visualized above a hyperechogenic density corresponding to tracheal cartilage. There was no sonographic evidence of cartilage disruption or adjacent lymphadenopathy. OCT revealed a layer of heterogeneous light backscattering suggesting the mucosal papilloma, and a layer of high degree scattering, corresponding to the central fibrovascular core noted on histology. CONCLUSIONS: Layered microstructures of RRP and underlying airway cartilage can be identified using a combination of acoustic and optical bronchoscopic imaging modalities with different resolution and depth of penetration characteristics.